2005
DOI: 10.1079/bjn20051463
|View full text |Cite
|
Sign up to set email alerts
|

The feeding route (enteral or parenteral) affects the plasma response of the dipetide Ala-Gln and the amino acids glutamine, citrulline and arginine, with the administration of Ala-Gln in preoperative patients

Abstract: Enhancement of depressed plasma concentrations of glutamine and arginine is associated with better clinical outcome. Supplementation of glutamine might be a way to provide the patient with glutamine, and also arginine, because glutamine provides the kidney with citrulline, from which the kidney produces arginine when plasma levels of arginine are low. The aim of the present study was to investigate the parenteral and enteral response of the administered dipeptide Ala-Gln, glutamine, citrulline and arginine. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 34 publications
3
63
2
7
Order By: Relevance
“…Th ese data have also been applied to enteral administration of supplementation, although enteral doses only marginally aff ect plasma concentration [10]- [12]. If the pharmaconutrition philosophy is applied, higher doses are usually given, although the rationale for doses beyond what may be needed to restore a low plasma concentration is purely hypothetical.…”
Section: Targets For Supplementationmentioning
confidence: 99%
“…Th ese data have also been applied to enteral administration of supplementation, although enteral doses only marginally aff ect plasma concentration [10]- [12]. If the pharmaconutrition philosophy is applied, higher doses are usually given, although the rationale for doses beyond what may be needed to restore a low plasma concentration is purely hypothetical.…”
Section: Targets For Supplementationmentioning
confidence: 99%
“…Little data are available comparing the metabolic effects of Gln when given by enteral versus parenteral routes (14,26). Also, metabolic results with enteral Gln administration have been inconsistent across studies (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that Gln supplementation in PN may be superior to the enteral route in terms of clinical outcomes [11] and repletion of plasma Gln [12]. However, in critically ill patients possessing active intestinal function and receiving EN, whether Gln should be given enterally or parenterally is not clear as data comparing the metabolic effects of intravenous Gln versus enteral Gln in critically ill patients are lacking [14][15]. Therefore, the purposes of this study were to compare metabolic effects of alanyl-Gln given by enteral and parenteral routes versus an unsupplemented control group and to obtain initial data on the potential effects of route of Gln administration.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in literature have been evaluating the effects of enteral and parenteral glutamine supplementation. Studies in critically ill patients and surgical patients showed that the parenteral administration was more effective in increasing plasma concentrations in relation to oral administration 16,17 . Another study in mice showed that when L-alanyl-L-glutamine was enterally administrated, there was a more significant increase for the synthesis of L-citrulline and L-arginine in relation to the parenteral administration 18 .…”
Section: Introductionmentioning
confidence: 99%